Metabolic model of necrotizing enterocolitis in the premature newborn gut resulting from enteric dysbiosis - Casaburi, Giorgio; Wei, Jingjing; Kazi, Sufyan; Liu, Junlin; Wang, Kewei; Tao, Guo-Zhong; Lin, Po-Yu; Dunn, James C. Y.; Henrick, Bethany M.; Frese, Steven A.; Sylvester, Karl G. (Frontiers in Pediatrics, 2022)
Necrotizing enterocolitis (NEC) is a leading cause of premature newborn morbidity and mortality. The clinical features of NEC consistently include prematurity, gut dysbiosis and enteral inflammation, yet the pathogenesis remains obscure. Herein we combine metagenomics and metabolomics, with functional in vivo and in vitro assessment, to define a novel molecular mechanism of NEC. 1,647 publicly available metagenomics datasets were analyzed (NEC = 245; healthy = 1,402) using artificial intelligence methodologies. Metabolomics was used to quantify the concentration of fecal metabolites at NEC onset, during recovery (n = 8), and in age matched controls (n = 10). Toxicity assays of discovered metabolites were performed in vivo in mice and in vitro using human intestinal epithelial cells. Metagenomic and metabolomic analyses revealed significant differences in pyruvate fermentation pathways and associated intermediates. Notably, the short chain fatty acid formate was elevated in the stool of NEC patients at disease onset (P = 0.005) dissipated during recovery (P = 0.02) and positively correlated with degree of intestinal injury (r2 = 0.86). In vitro, formate caused enterocyte cytotoxicity in human cells through necroptosis (P < 0.01). In vivo, luminal formate caused significant dose and development dependent NEC-like injury in newborn mice. Enterobacter cloacae and Klebsiella pneumoniae were the most discriminatory taxa related to NEC dysbiosis and increased formate production. Together, these data suggest a novel biochemical mechanism of NEC through the microbial production of formate. Clinical efforts to prevent NEC should focus on reducing the functional consequences of newborn gut dysbiosis associated metabolic pathways.